2017
DOI: 10.1039/c7ra09665h
|View full text |Cite
|
Sign up to set email alerts
|

A magnetic CoFe2O4–CNS nanocomposite as an efficient, recyclable catalyst for peroxymonosulfate activation and pollutant degradation

Abstract: Sulfate radical (SO 4 c À ) based advanced oxidation processes allow efficient degradation of refractory organics, but efficient, low-cost, and robust catalysts for such processes are still lacking. In this work, a magnetically recoverable heterogeneous catalyst was fabricated by immobilizing spinel cobalt-ferrite (CoFe 2 O 4 ) particles on graphitic carbon nitride nanosheets (CNS) using a low-cost, one-step solvothermal method. In the CoFe 2 O 4 -CNS nanocomposite, the CoFe 2 O 4 particles were evenlydistribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…These comparisons also suggested that the degradation extent of 4HBP was greatly correlated to MPS dosages as sulfate radicals are generated from MPS instead of catalysts. On the contrary, CSNF served as a catalyst which would manipulate degradation kinetics [56,57].…”
Section: Effects Of Csnf and Mps Dosages On 4hbp Degradationmentioning
confidence: 99%
“…These comparisons also suggested that the degradation extent of 4HBP was greatly correlated to MPS dosages as sulfate radicals are generated from MPS instead of catalysts. On the contrary, CSNF served as a catalyst which would manipulate degradation kinetics [56,57].…”
Section: Effects Of Csnf and Mps Dosages On 4hbp Degradationmentioning
confidence: 99%
“…This tended to reduce the contact area between the catalyst and other reactants, which was not conducive to pollutant removal (Xue et al, 2007). CuFe 2 O 4 -ST had a typical morphology of a solvothermal catalyst (Ueda Yamaguchi et al, 2016;Chen et al, 2017) with high dispersion, relatively uniform spherical-like shape, and minimum particle size, which could increase the external surface area. CuFe 2 O 4 -SG particles were found to be of moderate size and irregular shape.…”
Section: Sem Analysismentioning
confidence: 99%
“…[20] However, due to the high temperatures (> 900 °C) employed to overcome the diffusion barrier, it allows for little control over the preparation process and the homogeneity of the product. [20] Disadvantages of the solid-state synthesis are addressed by other methods, within so called "wet chemistry", such as solgel, [21,22] solvothermal [23] and hydrothermal synthesis, [24][25][26] reverse micelle synthesis, [27] polyol-assisted synthesis, [28] coprecipitation, [29][30][31] or the thermal decomposition of a suitable precursor. [18,[32][33][34] Among the listed methods the thermal decomposition presents an interesting option, as it offers the relative simplicity of the solid-state approach as well as the option to control the process due to relatively low temperatures that are involved.…”
Section: Introductionmentioning
confidence: 99%